Methodological aspects of human resources management in the context of the company's resource concept - O. A. Zyablikova (Вестник университета)
Modern organizations are forced to adapt to the conditions of market relations and competition. The factors that determine success in the market are also factors for the survival of the organization. Achieving competitive advantages in accordance with the resource approach is possible as a result of using unique resources, one of which is human resources. The most significant areas of interaction between the organization and the personnel within the framework of both the world community and the Russian Federation are considered in the article. A study of the provision of enterprises of the Penza region with human resources was carried out and an assessment of the effectiveness of the human resources management system in a pandemic was carried out using an expert method. Based on the results of the study, recommendations were developed for the organization of personnel management in conditions of uncertainty.